PENCURIAN PRATIMA DI BALI DALAM PERSPEKTIF HUKUM PIDANA ADAT - Angga Juniarta, Ida Bagus Gede; Sri Utari, Anak Agung (Kertha Wicara : Journal Ilmu Hukum, 2014)
The pratima thievery in Bali has become more frequently occured recently, and the solving process of the case is only using the Indonesia's formal criminal law with inadequate recognition to the criminal adat law as consideration. How the perspective of criminal adat law in the case of pratima thievery is significantly needed, to give the best consideration when it comes to the time of judiciary judgement. The method which is used in this paper is normative method, because norm conflict occurs when punishment in given. The discussion about pratima thievery can be studied from comparing the formal criminal law with criminal adat law in each region/villages. The criminal adat law oriented in a perspective which has purpose in the sanction given to the suspected, that it is not only giving detterent effect but also returning the cosmos balance within society.
Keywords: Theft, Pratima, Criminal Adat Law